Factors Influencing the Survival of Preformed Zirconia Crowns in Children Treated under General Anesthesia - Abdurahman S. Alhissan; Sharat Chandra Pani (International Journal of Dentistry)
Aim. This study aimed to retrospectively evaluate the success of zirconia crowns placed in the anterior teeth of children and evaluate the impact of pulp therapy of the tooth on the rate of failure. Materials and Methods. A total of 70 anterior teeth of 20 children aged between 3 and 5 years who had undergone the placement of zirconia crowns under general anesthesia were followed up for 24 months. Kaplan–Meier Survival curves were plotted for the estimation of two-year survival time. The outcomes for teeth that had received pulp therapy were compared to those that had not received pulp therapy. Results. Kaplan–Meier survival analysis of 70 crowns observed over a two-year period showed that mean survival time for the crowns was 38.7 months with a confidence interval ranging from 38.1 months to 39.3 months. When the survival of the crowns was observed based on the presence or absence of symptoms, it was observed that only 4 out of the 70 crowns were symptomatic (with or without crown loss) at the end of two years, giving a success rate of 94.3%. The mean survival time was also increased to 39.5 months (confidence interval 39.15–39.98 months). Conclusion. Zirconia crowns provide an acceptable level of success and longevity. Crowns placed on teeth after pulp therapy are more likely to fail than those placed on teeth without pulp therapy.